2022
DOI: 10.3390/ijms231810527
|View full text |Cite
|
Sign up to set email alerts
|

Ustilaginoidea virens Nuclear Effector SCRE4 Suppresses Rice Immunity via Inhibiting Expression of a Positive Immune Regulator OsARF17

Abstract: Rice false smut caused by the biotrophic fungal pathogen Ustilaginoidea virens has become one of the most important diseases in rice. The large effector repertory in U. virens plays a crucial role in virulence. However, current knowledge of molecular mechanisms how U. virens effectors target rice immune signaling to promote infection is very limited. In this study, we identified and characterized an essential virulence effector, SCRE4 (Secreted Cysteine-Rich Effector 4), in U. virens. SCRE4 was confirmed as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Previous studies revealed that the Ustilaginoidea virens- secreted effector SCRE4 inhibits the expression of the positive immune regulator OsARF17, thereby suppressing rice immunity 67 . However, the biological function of SCRE4 has not been fully understood.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies revealed that the Ustilaginoidea virens- secreted effector SCRE4 inhibits the expression of the positive immune regulator OsARF17, thereby suppressing rice immunity 67 . However, the biological function of SCRE4 has not been fully understood.…”
Section: Resultsmentioning
confidence: 99%
“…The gene replacement mutants were screened by PCR and were then confirmed by Southern blot analysis as described previously (Qiu et al., 2022 ). Briefly, genomic DNA was isolated through CTAB method.…”
Section: Methodsmentioning
confidence: 99%
“…Virulence assay was performed as described previously (Li et al, 2019;Qiu et al, 2022). Briefly, the wild-type, ΔUvhos3…”
Section: Virulence Assaymentioning
confidence: 99%
“…The effectors SCRE1 and UV_1261/SCRE2 inhibited highly sensitive cell death induced by the mouse proapoptotic protein Bax and Phytophthora infestans elicitin INF1, and they also inhibited immunity induced by pathogen-associated molecular patterns in rice [ 37 , 38 ]. Recent studies showed that the expression of the effector SCRE4 repressed the transcription of the immunopositive regulatory factor OsARF17 in U. virens , which promoted infection [ 39 ]. In addition, the effector SCRE6, a phosphatase of Aspergillus oryzae , interacted with rice mitogen-activated protein kinase 6 (OsMPK6) to dephosphorylate OsMPK6 and enhance its stability, thereby negatively regulating the rice immune response [ 40 ].…”
Section: Genomics and Effectors In Ustilaginoidea Virensmentioning
confidence: 99%